Effects of the usefulness of didactic principles in teaching history today - Boșcodeală, Felicia Elena (Technium Social Sciences Journal, 2022)
Current studies in the field of history as a science and as a discipline show us that it is in a permanent transformation, due to the increase in the level of complexity it entails, by reconsidering previous results and then by new methodological approaches. Our research is based on history as a didactic dimension and less on the history-science component, because as a discipline history has an important contribution to defining the cultural model in which people move, without particularities of age or gender, etc. Second, our analysis considers the constants and variables that have marked the discipline of history in the last 30 years.